Relieve in learning accounting / Anis Barieyah Mat Bahari - Mat Bahari, Anis Barieyah (2016)
Accounting is perceived as boring and dry subject. However, learning accounting may facilitate day to day activities. Furthermore, accounting helps students to polish their critical thinking skills and not focusing of the figures only. Thus, this paper may highlight a few techniques and approaches which may help facilitators or educators in making their classroom interesting especially in learning accounting. Sketching is one of enjoyable techniques to be used in learning accounting. In addition, the students able to strategize their way of understanding the accounting subject through sketching. This paper will highlight some benefits of sketching in teaching and learning process. Perhaps, it may give ideas in improving accounting teaching technique especially to those non accounting students.